2023
DOI: 10.1002/adma.202211624
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Amines with Gold Nanoparticles

Abstract: Understanding the interactions between amines and the surface of gold nanoparticles is important because of their role in the stabilization of the nanosystems, in the formation of the protein corona, and in the preparation of semisynthetic nanozymes. By using fluorescence spectroscopy, electrochemistry, X‐ray photoelectron spectroscopy, high‐resolution transmission electron microscopy, and molecular simulation, a detailed picture of these interactions is obtained. Herein, it is shown that amines interact with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 81 publications
(118 reference statements)
1
9
0
Order By: Relevance
“…The adsorption of AuNPs on antibody is reported to be caused by their nonspecific interactions, physical and/or chemical . The physical interactions include the electrostatic interaction between negatively charged tannic-acid-capped AuNPs and the positively charged region of the anti-IgG antibody, hydrophobic attraction between the planar aromatic moieties of tannic acid and the antibody chain, and hydrogen bond. Electrostatic interaction is reported to be the initial driving force of their attachment. , The charge distribution of an antimouse IgG monoclonal antibody has been reported in previous work, and it was found that the binding sites of the antibody are positively charged. , The structure of antimouse IgG monoclonal antibody used in our work remains confidential by the ELISA kit supplier, but it is assumed to share a charge distribution similar to that in the reference above, considering their similarity. Therefore, electrostatic interaction occurs between the anti-IgG antibody and tannic acids on AuNPs, which leads to soft attachment of AuNPs to the antibody.…”
Section: Resultssupporting
confidence: 94%
“…The adsorption of AuNPs on antibody is reported to be caused by their nonspecific interactions, physical and/or chemical . The physical interactions include the electrostatic interaction between negatively charged tannic-acid-capped AuNPs and the positively charged region of the anti-IgG antibody, hydrophobic attraction between the planar aromatic moieties of tannic acid and the antibody chain, and hydrogen bond. Electrostatic interaction is reported to be the initial driving force of their attachment. , The charge distribution of an antimouse IgG monoclonal antibody has been reported in previous work, and it was found that the binding sites of the antibody are positively charged. , The structure of antimouse IgG monoclonal antibody used in our work remains confidential by the ELISA kit supplier, but it is assumed to share a charge distribution similar to that in the reference above, considering their similarity. Therefore, electrostatic interaction occurs between the anti-IgG antibody and tannic acids on AuNPs, which leads to soft attachment of AuNPs to the antibody.…”
Section: Resultssupporting
confidence: 94%
“…S4†) indicated that PhaNPs(Ag(-)peptide(-)) can bind to bacteria by targeting surface thiols, reducing disulfide bridges to thiols, and bind to amine rich peptide sequences used by the bacteria for forming chain like structures. 73–75…”
Section: Resultsmentioning
confidence: 99%
“…NIC is an organic amine that can interact with the surface of Au(0) atoms of AuNPs through its lone electron pair. 40,41 The molecular form of NIC changes due to its different protonation degree in solution at different pH values. To investigate the existence form of NIC in different pH environments in detail, the p K a of the NIC molecule was simulated by using the quantitative structure–activity relationship (QSAR) model built using MarvinSketch software (Fig.…”
Section: Resultsmentioning
confidence: 99%